Aesthetic sphere in philosophical and intellectual reflections of the XXth century - N. I. Kovalova,; V. L. Levchenko, (Ukrainian Cultural Studies, 2018)
The article is devoted to the consideration of the aesthetical and the philosophical in intellectual reflections of the twentieth century. The material for the study were conceptions of such characteristic figures of modernism and postmodernism as W. Benjamin and J.-F. Lyotard. The task of the work was the analysis of modern and postmodern discourses and identification of their intertwining and intercollision.  Benjamin articulated main modernist tendencies in his writings. For him the sociological approach and the consideration of the subject of art and artistic activity in all manifestations were basic everywhere in analysis of art. Instead of these postmodern art reflects itself as an antisocialpractice in the context of it by the "decline of metanorations", the decline of ideology, the rejection of the general theoretical position, Modernism cuts off idea of any connection with the past. The principle condition on creativity for modernists was innovation and originality. Benjamin demonstrates such a level of decadence of the moderating guidelines in relation to the tradition. But for him Interest in historicity, games with citations in his books and writings are closed him to postmodernist positions and directions. Postmodernism, in relation to the past, is based on the paradigmic guideline that "everything was already there," everything has already happened both as an event and in an interpretive sense.
Keywords: modern, text, language, postmodern, knowledge, aesthetics